Asymmetric Bidirectional Controlled Teleportation via Seven-qubit Cluster State - Yang, Yu-Quan; Zha, Xin-Wei; Yu, Yan (International journal of theoretical physics, 2016)
We propose a new protocol of asymmetric bidirectional controlled teleportation by using a seven-qubit cluster state as the quantum channel. That is to say Alice wants to transmit an arbitrary single-qubit state to Bob and Bob wants to transmit an arbitrary two qubit state to Alice via the control of the supervisor Charlie. One only need perform the Bell-state measurements and single-qubit measurement.